2018
DOI: 10.1063/1.5040474
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field tuning of the valley splitting in silicon corner dots

Abstract: We perform an excited state spectroscopy analysis of a silicon corner dot in a nanowire field-effect transistor to assess the electric field tunability of the valley splitting. First, we demonstrate a back-gate-controlled transition between a single quantum dot and a double quantum dot in parallel that allows tuning the device in to corner dot formation. We find a linear dependence of the valley splitting on back-gate voltage, from 880 µeV to 610 µeV with a slope of −45 ± 3 µeV/V (or equivalently a slope of −4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Therefore, a reproducible and controllable valley splitting in silicon is on demand. Till now, several researches have been performed on valley splitting in silicon [162,[164][165][166][167][168]. As a whole, the valley splitting in quantum dots based on silicon MOS and SOI are in the range of 300-800 μeV and 610-880 μeV, respectively, and can be easily controlled by electric field [162,167].…”
Section: Materials Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a reproducible and controllable valley splitting in silicon is on demand. Till now, several researches have been performed on valley splitting in silicon [162,[164][165][166][167][168]. As a whole, the valley splitting in quantum dots based on silicon MOS and SOI are in the range of 300-800 μeV and 610-880 μeV, respectively, and can be easily controlled by electric field [162,167].…”
Section: Materials Developmentsmentioning
confidence: 99%
“…Till now, several researches have been performed on valley splitting in silicon [162,[164][165][166][167][168]. As a whole, the valley splitting in quantum dots based on silicon MOS and SOI are in the range of 300-800 μeV and 610-880 μeV, respectively, and can be easily controlled by electric field [162,167]. A recent research even suggested that the single-electron valley splitting in silicon MOS quantum dots is both tunable and predictable, thus silicon MOS is a promising platform for qubit control [165].…”
Section: Materials Developmentsmentioning
confidence: 99%
“…The smallest splittings, δ 20 ST and δ 11 ST Ã , may be associated with valley splittings, while the others involve combinations of valley and orbital excitations in QD mw . The relatively small δ 20 ST , which is associated with QD rf , is in the lower range of values reported for this class of devices (few tens to few hundreds of μeV [45][46][47][48][49]), which may be linked to a weak vertical electrical field and to the condition of the Si=SiO 2 interface. We note that the valley splitting may be enhanced by applying a negative back-gate voltage [47] or by reducing the number of electrons in the DQD, which strengthens vertical confinement.…”
Section: Magnetospectroscopymentioning
confidence: 65%
“…This allows bound electron states to accumulate, and creates a single QD. Corner dots [19,20] do not appear in the structure due to the narrow width of the channel. The FET top gate also acts as a plunger gate for the QD via capacitance C tg , allowing tuning of the next available energy level in the QD, which is labelled E QD , by adjusting V tg .…”
Section: Methodsmentioning
confidence: 99%